The Character Building of Educational Person Found in Novel " This Earth of Mankind" by Pramoedya Ananta Toer - Afrizal Afrizal Mukhtarom (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
ABSTRACTEducation, every person need an education to help in develop the souls of both physically and mentally from their nature towards a better human civilisation. And this process is continuous process that never stop (never ending process) so it can produce a sustainable one which is shown a future human. Every student has a different character and then came the character education/character building in the educational process. The character building have a purpose to develop the student potential to make them have a good mind, kind heart and the good attitude on student in behaviour. And this research are search the values for character building by using novel “This Earth of Mankind” by Pramoedya Ananta Toer as a media on educational process to build the character of the student. The value is taken from the dialog and monolog. Discourse analysis, about (data display, data reductive, data interpretative) is used to analysis data in this research. The result of the analysis that has been done, show about value as follows: (1)Love;(2)Curiosity;(3)Forgiving;(4)Hardwork;(5)Grateful;(6)Attitude;(7)Bravery;(8)Honest; (9)Responsibility;(10)Justice(11)Integrity;(12)Humble;(13)Positive Thinking.Keywords: Discourse analysis, education, character building, educational media.